Singing in signs new semiotic explorations of opera - Decker, Gregory John ca. 20./21. Jh; Shaftel, Matthew R. ca. 20./21. Jh (Oxford University Press, 2020)
Singing in Signs is a collection of essays from prominent opera scholars that explores the rich interplay of symbols in the operatic genre, while simultaneously providing perspective on the state of opera study. Each author, whether explicitly or implicitly, uses the powerful tools of semiotics (the study of signs) to construct interpretations and discover relationships among music, lyrics, and drama. Authors in this collection use a combination of traditional and emerging methodologies to engage composer - constructed and work-specific music - semiotic systems, broader sociocultural music codes, and narrative strategies. Many of the essays have implications for performance and staging.
Also issued in print: 2020. - Includes bibliographical references and index
Keywords: Opera; Semiotics; Musikalische Analyse; Oper; Semiotik; Aufsatzsammlung